CHAT GPT Y LA AUTOMATIZACION DE TAREAS ACADEMICAS EN LOS ESTUDIANTES DE LA CARRERA DE PEDAGOGIA DE LAS CIENCIAS EXPERIMENTALES INFORMATICA DE LA UNIVERSIDAD TECNICA DE BABAHOYO, PERIODO ACADEMICO OCTUBRE 2023 – MARZO 2024. - CABEZAS BAJAÑA LADDY KATHERINE (2024)
This research focuses on the use of ChatGPT and the automation of academic tasks in students. In itself, the ChatGPT artificial intelligence application is a very important resource that allows students to find out about a specific topic, in this way it can be said that it provides help when solving any type of academic task that the teacher sends to the student. having as its main objective that it be carried out correctly. When we talk about automation in education, we mean that it allows students to implement learning with the development of knowledge as its main objective. It also allows teaching between the teacher and the student to be more personalized and flexible at the time the lesson is being taught. class, it also provides the facility of being able to work inside and outside the classroom but together with the teachers and providing students with a better quality of teaching and learning. In this way, it can be said that the relationship between ChatGPT and task automation occurs because by working both together it allows students to use technology as a main resource that will be very helpful when carrying out any academic activity and also encourages the creative thinking of each of the students because it allows them to investigate any topic that they are not clear about and thus be able to have a clear hypothesis of what is being investigated.